2004
DOI: 10.1080/01460860490497778
|View full text |Cite
|
Sign up to set email alerts
|

Quality in Pediatric Nursing Care: Children's Expectations

Abstract: Children's perceptions of pediatric nursing care have not been systematically taken into account in the development of the quality of care. Usually, parents have evaluated children's care and its quality. The purpose of this study was to examine children's expectations concerning the quality of pediatric nursing care by interviewing 20 preschool and 20 school-aged children in Finland. Twenty of them had insulindependent diabetes mellitus (IDDM) and visited the hospital on a regular basis, and 20 were treated o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
64
0
8

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 28 publications
4
64
0
8
Order By: Relevance
“…Countless studies (2,(6)(7)(8)(9)(10)(11)(12)(13) have focused on the promotion of playing and toys as a therapeutic resource, and it can be an instrument to facilitate the integrality of care, treatment adherence, maintaining the child's rights (7) and establishing more appropriate communication channels (7,16) . As the organization of child health care should contemplate different scenarios, in this study, we attempted to look at children in an outpatient waiting room.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Countless studies (2,(6)(7)(8)(9)(10)(11)(12)(13) have focused on the promotion of playing and toys as a therapeutic resource, and it can be an instrument to facilitate the integrality of care, treatment adherence, maintaining the child's rights (7) and establishing more appropriate communication channels (7,16) . As the organization of child health care should contemplate different scenarios, in this study, we attempted to look at children in an outpatient waiting room.…”
Section: Discussionmentioning
confidence: 99%
“…This research aims to understand the experience of playing, from the perspective of children and their companions, after having participated in the activities of this intervention project. In this study, we justify the focus on playing in the outpatient context, as most research reported in literature (2,(6)(7)(8)(9)(10)(11)(12)(13) refers to the use of this resource in hospitalization situations only. However, care delivery to children in outpatient clinics should also incorporate interventions that value humanization and the child development process.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that describe quality of care from the patient's perspective list good relations with health professionals and adequate information as important factors for both patients and relatives [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…These results together with Cetinkaya and Kurt which indicates that the quality of life of children leukemia after providing information increased significantly compared with before giving the information. 20 When a child is sick, the whole family must make adjustments to the new lifestyle includes a wide range of pain-related tasks. During the hospitalization of children require entertainment, maintenance, security, information and participation.…”
mentioning
confidence: 99%